18F-FDG PET/CT reveals disease remission in a patient with ipilimumab-refractory advanced melanoma treated with pembrolizumab - Sachpekidis, Christos; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (Clinical nuclear medicine, 2016)
Pembrolizumab is an anti-programmed cell death receptor 1 (anti-PD-1) antibody, recently approved for the treatment of ipilimumab-refractory metastatic melanoma. We report on a 49-year-old patient with unresectable metastatic melanoma initially treated with 4 cycles of ipilimumab. Because of demonstration of progressive disease on PET/CT, the patient was enrolled into a clinical trial of pembrolizumab. After completion of 4 cycles of pembrolizumab, the follow-up PET/CT scans performed early after and 7 months after the end of treatment exhibited complete disease remission, reflecting the potential role of the modality in treatment response evaluation of melanoma patients receiving anti-PD-1 therapy.
Gesehen am 07.05.2020